Microbes, the ‘silent third partners’ of bee–angiosperm mutualisms - Shawn A. Steffan; Prarthana S. Dharampal; Jordan G. Kueneman; Alexander Keller; Magda P. Argueta-Guzmán; Quinn S. McFrederick; Stephen L. Buchmann; Rachel L. Vannette; Anna F. Edlund; Celeste C. Mezera; Nolan Amon; Bryan N. Danforth (Trends in Ecology & Evolution, 2024)

CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

The diversification of neopasiphaeine bees during the Cenozoic (Hymenoptera: Colletidae) - Eduardo A. B. Almeida; Laurence Packer; Gabriel A. R. Melo; Bryan N. Danforth; Sophie C. Cardinal; Fábio B. Quinteiro; Marcio R. Pie (Zoologica Scripta, 2019)
The biogeography of colletid bees as a whole can be explained by several South American‐Australian trans‐Antarctic interchanges. Within Colletidae, neopasiphaeine bees form a large group that has not been adequately studied, even though they are interesting both from the biogeographical viewpoint for fitting well the austral Gondwanan track and for their associations to host plants. The present paper integrates phylogenetic, biogeographic and paleontological data to reconstruct the evolutionary history of Neopasiphaeinae, with special emphasis on the New World taxa, relating the evolution of these bees to changes, such as the Andes uplift and expansion of open vegetation biomes. First, we propose a phylogenetic hypothesis for the Neopasiphaeinae using one mitochondrial and five nuclear loci. Phylogenetic relationships and divergence time estimation were simultaneously inferred in a Bayesian framework, and the tempo of neopasiphaeine diversification was investigated using lineage‐through‐time plots. The historical biogeography of neopasiphaeine bees was investigated in a likelihood framework. The clade represented by Neopasiphaeinae is strongly supported within Colletidae, and the bulk of their genera can be divided into two major sister‐clades that diverged during the Eocene: one endemic to the Australian region and the other to the Neotropical region. Divergence times among most neotropical genera of Neopasiphaeinae indicate that they differentiated and started their diversification during the Miocene. Our results depict a complex process of geographic evolution in the Neotropical clade, which probably relates to important changes in the neotropical climates and biota beginning at the Oligocene and became more marked in the Miocene. We present a scenario of the neotropical Neopasiphaeinae initially associated with areas of open vegetation in subtropical and temperate portions of South America, followed by multiple separations of lineages east and west of the Andes, and more recent occupations of habitats in tropical portions of the continent.

Viral transmission in honey bees and native bees, supported by a global black queen cell virus phylogeny - Elizabeth A. Murray; John Burand; Natalia Trikoz; Julia Schnabel; Heather Grab; Bryan N. Danforth (Environmental Microbiology, 2019)
Summary In recent decades, we have realized that honey bee viruses are not, in fact, exclusive to honey bees. The potential impact of Apis ‐affiliated viruses on native pollinators is prompting concern. Our research addresses the issue of virus crossover between honey bees and native bees foraging in the same localities. We measured the presence of black queen cell virus (BQCV), deformed wing virus (DWV) and sacbrood virus (SBV) in managed Apis mellifera (honey bees) and native Andrena spp. (subgenus Melandrena ) bee populations in five commercial orchards. We identified viral presence across sites and bees and related these data to measures of bee community diversity. All viruses were found in both managed and native bees, and BQCV was the most common virus in each. To establish evidence for viral crossover between taxa, we undertook an additional examination of BQCV where 74 samples were sequenced and placed in a global phylogenic framework of hundreds of BQCV strains. We demonstrate pathogen sharing across managed honey bees and distantly related wild bees. This phylogenetic analysis contributes to growing evidence for host switching and places local incidence patterns in a worldwide context, revealing multispecies viral transmission.

Climate, physiological tolerance and sex‐biased dispersal shape genetic structure of N eotropical orchid bees - Margarita M. López‐Uribe; Kelly R. Zamudio; Carolina F. Cardoso; Bryan N. Danforth (Molecular Ecology, 2014)
Understanding the impact of past climatic events on the demographic history of extant species is critical for predicting species' responses to future climate change. Palaeoclimatic instability is a major mechanism of lineage diversification in taxa with low dispersal and small geographical ranges in tropical ecosystems. However, the impact of these climatic events remains questionable for the diversification of species with high levels of gene flow and large geographical distributions. In this study, we investigate the impact of P leistocene climate change on three N eotropical orchid bee species ( E ulaema bombiformis , E . meriana and E . cingulata ) with transcontinental distributions and different physiological tolerances. We first generated ecological niche models to identify species‐specific climatically stable areas during P leistocene climatic oscillations. Using a combination of mitochondrial and nuclear markers, we inferred calibrated phylogenies and estimated historical demographic parameters to reconstruct the phylogeographical history of each species. Our results indicate species with narrower physiological tolerance experienced less suitable habitat during glaciations and currently exhibit strong population structure in the mitochondrial genome. However, nuclear markers with low and high mutation rates show lack of association with geography. These results combined with lower migration rate estimates from the mitochondrial than the nuclear genome suggest male‐biased dispersal. We conclude that despite large effective population sizes and capacity for long‐distance dispersal, climatic instability is an important mechanism of maternal lineage diversification in orchid bees. Thus, these N eotropical pollinators are susceptible to disruption of genetic connectivity in the event of large‐scale climatic changes.

Biodiversity ensures plant–pollinator phenological synchrony against climate change - Ignasi Bartomeus; Mia G. Park; Jason Gibbs; Bryan N. Danforth; Alan N. Lakso; Rachael Winfree (Ecology Letters, 2013)
Climate change has the potential to alter the phenological synchrony between interacting mutualists, such as plants and their pollinators. However, high levels of biodiversity might buffer the negative effects of species‐specific phenological shifts and maintain synchrony at the community level, as predicted by the biodiversity insurance hypothesis. Here, we explore how biodiversity might enhance and stabilise phenological synchrony between a valuable crop, apple and its native pollinators. We combine 46 years of data on apple flowering phenology with historical records of bee pollinators over the same period. When the key apple pollinators are considered altogether, we found extensive synchrony between bee activity and apple peak bloom due to complementarity among bee species’ activity periods, and also a stable trend over time due to differential responses to warming climate among bee species. A simulation model confirms that high biodiversity levels can ensure plant–pollinator phenological synchrony and thus pollination function.

A global quantitative synthesis of local and landscape effects on wild bee pollinators in agroecosystems - Christina M. Kennedy; Eric Lonsdorf; Maile C. Neel; Neal M. Williams; Taylor H. Ricketts; Rachael Winfree; Riccardo Bommarco; Claire Brittain; Alana L. Burley; Daniel Cariveau; Luísa G. Carvalheiro; Natacha P. Chacoff; et al. (Ecology Letters, 2013)
Bees provide essential pollination services that are potentially affected both by local farm management and the surrounding landscape. To better understand these different factors, we modelled the relative effects of landscape composition (nesting and floral resources within foraging distances), landscape configuration (patch shape, interpatch connectivity and habitat aggregation) and farm management (organic vs. conventional and local‐scale field diversity), and their interactions, on wild bee abundance and richness for 39 crop systems globally. Bee abundance and richness were higher in diversified and organic fields and in landscapes comprising more high‐quality habitats; bee richness on conventional fields with low diversity benefited most from high‐quality surrounding land cover. Landscape configuration effects were weak. Bee responses varied slightly by biome. Our synthesis reveals that pollinator persistence will depend on both the maintenance of high‐quality habitats around farms and on local management practices that may offset impacts of intensive monoculture agriculture.

Identifying the sister group to the bees: a molecular phylogeny of Aculeata with an emphasis on the superfamily Apoidea - Andrew H. Debevec; Sophie Cardinal; Bryan N. Danforth (Zoologica Scripta, 2012)
Debevec, AH., Cardinal, S & Danforth, BN. Identifying the sister group to the bees: a molecular phylogeny of Aculeata with an emphasis on the superfamily Apoidea. — Zoologica Scripta , 41 , 527–535. The hymenopteran superfamily Apoidea includes the bees (Anthophila) as well as four predatory wasp families (Heterogynaidae, Ampulicidae, Sphecidae and Crabronidae) collectively referred to as the “sphecoid” or “apoid” wasps. The most widely cited studies suggest that bees are sister to the wasp family Crabronidae, but alternative hypotheses have been proposed based on both morphological and molecular data. We combined DNA sequence data from previously published studies and newly generated data for four nuclear genes (28S, long‐wavelength rhodopsin, elongation factor‐1α and wingless ) to identify the likely sister group to the bees. Analysis of our four‐gene data set by maximum likelihood and Bayesian methods indicates that bees most likely arise from within a paraphyletic Crabronidae. Possible sister groups to the bees include Philanthinae, Pemphredoninae or Philanthinae + Pemphredoninae. We used Bayesian methods to explore the robustness of our results. Bayes Factor tests strongly rejected the hypotheses of crabronid monophyly as well as placement of Heterogynaidae within Crabronidae. Our results were also stable to alternative rootings of the bees. These findings provide additional support for the hypothesis that bees arise from within Crabronidae, rather than being sister to Crabronidae, thus altering our understanding of bee ancestry and evolutionary history.

Biogeography and diversification of colletid bees (Hymenoptera: Colletidae): emerging patterns from the southern end of the world - Eduardo A. B. Almeida; Marcio R. Pie; Seán G. Brady; Bryan N. Danforth (Journal of Biogeography, 2012)
Aim The evolutionary history of bees is presumed to extend back in time to the Early Cretaceous. Among all major clades of bees, Colletidae has been a prime example of an ancient group whose Gondwanan origin probably precedes the complete break‐up of Africa, Antarctica, Australia and South America, because modern lineages of this family occur primarily in southern continents. In this paper, we aim to study the temporal and spatial diversification of colletid bees to better understand the processes that have resulted in the present southern disjunctions. Location Southern continents. Methods We assembled a dataset comprising four nuclear genes of a broad sample of Colletidae. We used Bayesian inference analyses to estimate the phylogenetic tree topology and divergence times. Biogeographical relationships were investigated using event‐based analytical methods: a Bayesian approach to dispersal–vicariance analysis, a likelihood‐based dispersal–extinction–cladogenesis model and a Bayesian model. We also used lineage through time analyses to explore the tempo of radiations of Colletidae and their context in the biogeographical history of these bees. Results Initial diversification of Colletidae took place at the Late Cretaceous (≥ 70 Ma). Several (6–14) lineage exchanges between Australia and South America via Antarctica during the Late Cretaceous and Eocene epochs could explain the disjunctions observed between colletid lineages today. All biogeographical methods consistently indicated that there were multiple lineage exchanges between South America and Australia, and these approaches were valuable in exploring the degree of uncertainty inherent in the ancestral reconstructions. Biogeographical and dating results preclude an explanation of Scrapterinae in Africa as a result of vicariance, so one dispersal event is assumed to explain the disjunction in relation to Euryglossinae. The net diversification rate was found to be highest in the recent history of colletid evolution. Main conclusions The biogeography and macroevolutionary history of colletid bees can be explained by a combination of Cenozoic vicariance and palaeoclimatic changes during the Neogene. The austral connection and posterior break‐up of South America, Antarctica and Australia resulted in a pattern of disjunct sister lineages. Increased biome aridification coupled with floristic diversification in the southern continents during the Neogene may have contributed to the high rates of cladogenesis in these bees in the last 25–30 million years.

Isolation and cross-species characterization of polymorphic microsatellites for the orchid bee Eulaema meriana (Hymenoptera: Apidae: Euglossini) - Margarita M. López-Uribe; Amy N. Green; Santiago R. Ramírez; Steve M. Bogdanowicz; Bryan N. Danforth (Conservation Genetics Resources, 2011)

The morphology and behavior of dimorphic males in Perdita portalis (Hymenoptera : Andrenidae) - Bryan N. Danforth (Behavioral Ecology and Sociobiology, 1991)